Influence of infrastructure and info structure, curriculum, pedagogy and content in teaching and learning through MOOCs - Kamal Abdul Nasir, Nur Azlinda Kasma Azizan; Ab. Jalil, Habibah; Mahmud, Rosnaini (Human Resource Management Academic Research Society, 2017)
In Malaysia, Massive Open Online Course (MOOC) is an emerging approach in the higher education teaching and learning which takes the new role of technology to the next level. However, the successful implementation of MOOC requires effective strategic planning and understanding of the whole process involved. This study investigates the influence of infrastructure and info structure, curriculum, pedagogy, and content towards enhancement in teaching and learning in Massive Open Online Courses (MOOCs) in one of the common course offered in Malaysian Public Universities. This study examines the pilot data from a bigger dataset collected from an online survey. Collected data was analyzed using Structural Equation Modeling (SEM), to propose a model of enhancement in teaching and learning through MOOCs. Preliminary analysis shows that infrastructure and info structure, curriculum, pedagogy, content, and enhancement in teaching and learning were significantly correlated to each other. The overall contribution of this model which to enhancement in teaching and learning was 13.0%. The model summarized that only curriculum construct influence the enhancement in teaching and learning (β=0.244; p<0.01) make it as the sole contributor for this model.